DESINDUSTRIALIZAÇÃO DA ECONOMIA BRASILEIRA: Uma análise das evidências para o período de 1990 a 2010 - Rodrigues, Marlana Portilho (2014)
This study aims to verify the existence of de-industrialization in the Brazilian economy in the period 1990-2010. To do so, we attempted to analyze the phenomenon in accordance with current national and international literature screen. In this sense, the objective is to ascertain if there is evidence that if the country is de-industrializing through analysis recommended by the various authors who have studied the subject data. The analysis of deindustrialization included three perspectives (Product, employment and external sector), which demonstrated the existence of this phenomenon in the country, whose causes are much more complex, going beyond the currency appreciation as advocated by leading theorists, and encompassing the density and loss of productive changes and errors in economic policy, especially after 1990.